Aplikasi Peralatan Flexible AC transmission Systems (FACTS) Pada Sistem Tenaga Listrik - Misba, Misbahuddin Buang (JNSTA ADPERTISI JOURNAL, 2024)
The power need of South Sulawesi community is increasingly in a row with technology development. At this time, with the lack of new generation and transmission facilities make voltage instability always occur. To relieve it, Flexible AC Transmission System (FACTS) is used, that is, Static Compensator (STATCOM) which its basic operating principles functions as a synchronous voltage source. This research aimed to  find out  voltage conditions and power systems losses of South Sulawesi before and after using STATCOM and determine location of STATCOM installation. This research was carried out in South Sulawesi region specially at PT. PLN (Ltd.) Business Unit of SULSELTRABAR. To determined location of STATCOM installation, Trial and Error Method is used where buses which have voltage exist near to voltage interval limit allowed, became a reference of STATCOM installation. The results shows that voltage condition before STATCOM installed, exist to voltage interval limit allowed, that is, 0.95 – 1.05 pu. However, voltage of Tonasa Tonasa, Bontoala, Pangkep70, and Tallo Lama buses exist near to voltage interval limit allowed. Based on simulation results, an exact STATCOM installation is on two buses, that is, Tonasa and Bontoala buses until voltage of mentioned four buses are improved and near to fundamental voltage, respectively. Power losses after STATCOM installed is increase because when it installed, there are conduction losses and switching losses at STATCOM